Virtualization of E-Health Communication Media on E-Health Halodoc - Mikhael Yulius Cobis; Iren Ayu Nindi (Jurnal Mutakallimin : Jurnal Ilmu Komunikasi, 2022)
Especially in times of pandemic, health is very important and irreplaceable. People often seek health information through health communications media. Various forms of health communication compete to spread their wings and evolve to provide the best information. Health magazines are one of the health communication media that provide information on health and healthy lifestyles, followed by various radio stations and television programs. With the development of technology, including the Internet, digital media providing health information has also become prevalent, from simple health information portals to virtual media in the form of applications that enable two-way interaction. This research literature review focuses on mass media and its development, the development of the Internet and its application to the Halodoc electronic health media platform. Globalization is also the reason behind the development of the Internet. The researcher also describes four eras with the best means of communicating time and technological determinism. There are pros and cons to using e-Health Halodoc as your e-Health media platform. The results of this research prove that Internet development and technology can not be separated. These two things play an important role in mutual development, especially in medical media.